C2 IgM Natural Antibody Enhances Inflammation and Its Use in the Recombinant Single Chain Antibody-Fused Complement Inhibitor C2-Crry to Target Therapeutics to Joints Attenuates Arthritis in Mice - Banda, Nirmal K.; Tomlinson, Stephen; Scheinman, Robert I.; Ho, Nhu; Ramirez, Joseline Ramos; Mehta, Gaurav; Wang, Guankui; Vu, Vivian Pham; Simberg, Dmitri; Kulik, Liudmila; Holers, V. Michael (Frontiers in Immunology, 2020)
Natural IgM antibodies (NAbs) have been shown to recognize injury-associated neoepitopes and to initiate pathogenic complement activation. The NAb termed C2 binds to a subset of phospholipids displayed on injured cells, and its role(s) in arthritis, as well as the potential therapeutic benefit of a C2 NAb-derived ScFv-containing protein fused to a complement inhibitor, complement receptor-related y (Crry), on joint inflammation are unknown. Our first objective was to functionally test mAb C2 binding to apoptotic cells from the joint and also evaluate its inflammation enhancing capacity in collagen antibody-induced arthritis (CAIA). The second objective was to generate and test the complement inhibitory capacity of C2-Crry fusion protein in the collagen-induced arthritis (CIA) model. The third objective was to demonstrate in vivo targeting of C2-Crry to damaged joints in mice with arthritis. The effect of C2-NAb on CAIA in C57BL/6 mice was examined by inducing a suboptimal disease. The inhibitory effect of C2-Crry in DBA/1J mice with CIA was determined by injecting 2x per week with a single dose of 0.250 mg/mouse. Clinical disease activity (CDA) was examined, and knee joints were fixed for analysis of histopathology, C3 deposition, and macrophage infiltration. In mice with suboptimal CAIA, at day 10 there was a significant (p < 0.017) 74% increase in the CDA in mice treated with C2 NAb, compared to mice treated with F632 control NAb. In mice with CIA, at day 35 there was a significant 39% (p < 0.042) decrease in the CDA in mice treated with C2-Crry. Total scores for histopathology were also 50% decreased (p < 0.0005) in CIA mice treated with C2-Crry. C3 deposition was significantly decreased in the synovium (44%; p < 0.026) and on the surface of cartilage (42%; p < 0.008) in mice treated with C2-Crry compared with PBS treated CIA mice. Furthermore, C2-Crry specifically bound to apoptotic fibroblast-like synoviocytes in vitro, and also localized in the knee joints of arthritic mice as analyzed by in vivo imaging. In summary, NAb C2 enhanced arthritis-related injury, and targeted delivery of C2-Crry to inflamed joints demonstrated disease modifying activity in a mouse model of human inflammatory arthritis.